2010
DOI: 10.2337/dc09-0542
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Protein D, a Marker of Lung Innate Immunity, Is Positively Associated With Insulin Sensitivity

Abstract: OBJECTIVEImpaired lung function and innate immunity have both attracted growing interest as a potentially novel risk factor for glucose intolerance, insulin resistance, and type 2 diabetes. We aimed to evaluate whether surfactant protein D (SP-D), a lung-derived innate immune protein, was behind these associations.RESEARCH DESIGN AND METHODSSerum SP-D was evaluated in four different cohorts. The cross-sectional associations between SP-D and metabolic and inflammatory parameters were evaluated in two cohorts, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 25 publications
(38 reference statements)
5
47
0
Order By: Relevance
“…As shown in Table 6, age (Beta = 0.36, p < 0.001), and steroid intake (Beta = −0.36, p < 0.001) and rs3088308 influence serum SP-D levels (Beta = −0.33, p < 0.001) along with exacerbation status (Beta = 0.28, p = 0.01), body mass index (Beta = −0.26, p = 0.01) and SNP rs721917 (Beta = −0.21, p = 0.03). Our study supports the previous studies correlating age [29], body mass index [31,32], corticosteroid intake [33] and rs721917 [29,31,39] with systemic SP-D levels. We have previously reported on significantly raised serum SP-D levels in COPD exacerbations [34].…”
Section: Discussionsupporting
confidence: 81%
“…As shown in Table 6, age (Beta = 0.36, p < 0.001), and steroid intake (Beta = −0.36, p < 0.001) and rs3088308 influence serum SP-D levels (Beta = −0.33, p < 0.001) along with exacerbation status (Beta = 0.28, p = 0.01), body mass index (Beta = −0.26, p = 0.01) and SNP rs721917 (Beta = −0.21, p = 0.03). Our study supports the previous studies correlating age [29], body mass index [31,32], corticosteroid intake [33] and rs721917 [29,31,39] with systemic SP-D levels. We have previously reported on significantly raised serum SP-D levels in COPD exacerbations [34].…”
Section: Discussionsupporting
confidence: 81%
“…High-quality total RNA (4 mg) was reverse-transcribed with the use of a (dT) 18 primer and RevertAid TM H Minus MMuLV reverse transcriptase (Fermentas, Lithuania), according to the manufacturer's recommendations. The levels of NOS2 and SFTPD transcripts were analyzed by quantitative real time PCR (qRT-PCR) with the use of Maxima TM SYBR Green/ROX qPCR Master Mix (2 x) (Thermo Scientific, United States) and specific primers for NOS2, SFTPD, and glyceraldehyde 3-phosphate dehydrogenase (GAPDH) as a housekeeping gene.…”
Section: Gene Expression Assaymentioning
confidence: 99%
“…In fact, decreased serum SP-D concentration has been reported in subjects with obesity and T2DM and it negatively correlates with fasting and post-load serum glucose. 18 Additionally, SFTPD gene polymorphisms have been found to associate with insulin resistance and T2DM. 19 Although a great deal of information concerning the relationship between immune-related genes such as NOS2 and SFTPD, and diabetes including T1DM and T2DM has been gained in recent years, no progress has been made toward understanding their significance in leukocytes obtained from GDM patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fernández-Real (2008) found that SP-A levels in the blood were significantly higher among patients with glucose intolerance and type 2 diabetes than in those with normal glucose tolerance, even after adjustment for BMI, age, and smoking status. Additionally, SP-D, a lung-derived innate immune protein, is also associated with inflammation and metabolic abnormalities including insulin sensitivity [Fernández-Real, 2010]. Indeed, in the obese type 2 diabetes animal model, many qualitatively similar changes as in type 1 diabetes develop with extensive lipid deposition, altered alveolar type-2 cell ultrastructure and surfactant protein expression patterns [Foster, 2010].…”
Section: Possible Underlying Mechanismsmentioning
confidence: 99%